Pendidikan Kesehatan tentang Meningkatkan Kebugaran Jasmani pada Lansia Di RW III Kebraon, Karang Pilang Surabaya - Dwi Purwantini; Kresna Adji Kurniawan (Jurnal Abdimas Kesehatan (JAK), 2022)
The covid-19 pandemic situation has occurred more than 1 year, so many people do not do much activities outdoor. This has impact on the health and physical fitness of the elderly in RW III, Kebraon, Karang Pilang Surabaya. Objective: Health education about effort to improve physical fitness in the elderly can be a solution to improve the qualityof life of the elderly during a pandemic. Methods: used in this communityservice are lectures, leaflet, and question and answers. This community service is carried out for elderly in RW III Kebraon, Karang Pilang, Surabaya. 30 elderly and elderly posyandu cadre participated in this activity. Result: the result obtained in this community service were an increase in behavioral aspects of knowledge about physical fitness increased by 100%, types of physical activity that can improve physical fitness in increased 93%, elderly who understood the benefit of physical activity increased 87%, and 63% of the elderly would do physical activity in accordance with the appropriate dose. Based on the result ont community service, it can be concluded that helath education is very effective, thereby increasing the elderly’s understanding of the benefits of exercise and physical activity, type of activity and dose of the exercise that can improve physical fitness in the elderly